2013
DOI: 10.1021/ie303354j
|View full text |Cite
|
Sign up to set email alerts
|

Elution of Hexavalent Chromium from Molten Sewage Sludge Slag: Influence of Sample Basicity and Cooling Rate

Abstract: Sewage sludge generated from sewage treatment plants sometimes contains chromium, and to prevent its release to the environment, it is necessary for the sludge to undergo high-temperature treatment. The molten slag treatment method is one such option. The chemical form of chromium in slag can be influenced not only by oxygen potential but also by temperature, basicity of slag, and other treatment operations. We have investigated the effect of sample basicity and cooling rate on the elution of hexavalent chromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Leaching tests conducted by Cao et al 17 revealed that the formation of the spinel phase can limit the leaching amount of Cr, while the Cr present in the silicate and periclase phases can be readily dissolved into the leachate. In other works with various cooling rates, rapid quenching to the amorphous glass phase have been found to encapsulate Cr ions, which could inhibit the dissolution of Cr, 19,20 but others deemed metastable phases, which can be readily generated during quenching, are unconducive to Cr stabilization 21 . Unfortunately, fundamental works on the dissolution behavior of Cr from simple spinel phases involving MnCr 2 O 4 , MgCr 2 O 4 , and FeCr 2 O 4 with higher Cr enrichment ratios and the stability of Cr during leaching in modified Cr‐containing slags are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Leaching tests conducted by Cao et al 17 revealed that the formation of the spinel phase can limit the leaching amount of Cr, while the Cr present in the silicate and periclase phases can be readily dissolved into the leachate. In other works with various cooling rates, rapid quenching to the amorphous glass phase have been found to encapsulate Cr ions, which could inhibit the dissolution of Cr, 19,20 but others deemed metastable phases, which can be readily generated during quenching, are unconducive to Cr stabilization 21 . Unfortunately, fundamental works on the dissolution behavior of Cr from simple spinel phases involving MnCr 2 O 4 , MgCr 2 O 4 , and FeCr 2 O 4 with higher Cr enrichment ratios and the stability of Cr during leaching in modified Cr‐containing slags are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Sakai [3] investigated the effect of sample basicity and cooling rate on the elution of hexavalent chromium from molten sewage sludge slag and confirmed that low sample basicity (less than 0.9) and rapid cooling were effective to prevent elution of hexavalent chromium from molten slag samples. Galina [4,5] investigated the effect of the cooling system on the occurrence state of chromium in the CaO–SiO 2 –MgO–Cr 2 O 3 synthesis slag.…”
Section: Introductionmentioning
confidence: 99%